2019
DOI: 10.1021/acs.jpcc.9b03296
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Isoenergetic Band Alignment between CdS QDs and CaFe2O4@ZnFe2O4 Heterojunction: A Promising Ternary Hybrid toward Norfloxacin Degradation and H2 Energy Production

Abstract: The increasing demand for clean water triggers advancement in development of nanomaterials for photocatalytic pollutant degradation. Herein, we report for the first time a CdS QDs decorated p-CaFe 2 O 4 @n-ZnFe 2 O 4 heterojunction photocatalyst fabricated via a two-step chemical route, i.e. sol−gel auto combustion and precipitationdeposition methods. The prepared photocatalyst proves to be effective toward degradation of the emerging pollutant norfloxacin under solar light irradiation. Systematic analysis inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 60 publications
0
27
0
2
Order By: Relevance
“…CdS quantum dots decorated by CaFe2O4@ZnFe2O4 prepared by sol-gel auto combustion followed by deposition method and 83% of norfloxacin photodegraded in 90 min under solar irradiation [75]. The maximum degradation were noticed at pH=3, at this pH norfloxacin exist as positively charged species whereas, at this pH heterojunction surface is negatively charged about -12.07 mV as confirmed by zeta potential analysis.…”
Section: Type-ii Based Ferrite Heterojunctionmentioning
confidence: 63%
“…CdS quantum dots decorated by CaFe2O4@ZnFe2O4 prepared by sol-gel auto combustion followed by deposition method and 83% of norfloxacin photodegraded in 90 min under solar irradiation [75]. The maximum degradation were noticed at pH=3, at this pH norfloxacin exist as positively charged species whereas, at this pH heterojunction surface is negatively charged about -12.07 mV as confirmed by zeta potential analysis.…”
Section: Type-ii Based Ferrite Heterojunctionmentioning
confidence: 63%
“…As shown in Figure 3B, the peak located at 530.6 eV could be attributed to the lattice oxygen of NiO (Wang et al, 2010;Liu et al, 2012;Hu et al, 2018). Figure 3C displays the high-resolution XPS spectra of Cd 3d; the binding energies at 405.2 and 411.9 eV correspond to the Cd 3d 5/2 and Cd 3d 3/2 of the Cd 2+ in CdS nanorods, respectively (Bai et al, 2010;Zhou P. et al, 2017;Behera et al, 2019). The XPS spectrum of S (Figure 3D) presents two peaks at 162.8 and 161.7 eV that were assigned to the characteristic binding energies of S 2p 1/2 and S 2p 3/2 of S 2− .…”
Section: Synthesis and Characterizationmentioning
confidence: 94%
“…Numerous researches had found that semiconductor photocatalytic technology can be efficacious means of solving the growing environmental pollution and energy crisis around the world [4][5][6][7]. However, common photocatalyst are limited in application for narrow light absorption range, poor stabilization, and lower photodegradation efficiency [8,9].…”
Section: Introductionmentioning
confidence: 99%